(The Impact of Traffic Accidents on Development: A Contemporary Accounting Perspective, Asir governorate as a model - Saudi Arabia (2006-2013 - Abdullah, Shahabuddin Mohammed Ahmed (Arab Journal for Sciences and Research Publishing, 2017)
The traffic accidents in the high ways and towns are still increasing, their effect on the community development clearly seen. The control of this problem is highly significant. The analysis of the data and the information about the traffic accidents, their direct, indirect, a variables and continues cost represented in curing the injured, paying the Diya, the cost of the medical operations on behalf of the government and the relatives of the injured dealt with through the accounting view. This paper aimed at measuring the effect of traffic accidents in terms of money, to be use for the development of Accer province – South of the kingdom of Saudi Arabia. The overall cost of the traffic accidents in 2013 is 23 pillions Riyal. The percentage of the injured is 30% per family. The cost account of traffic accidents in Accer province is 1. 6 pillions Riyal. These sums of money could have been use for the development of the province. The paper recommends The direct, indirect, a variables and continues costs of the traffic accidents should give a due consideration The traffic administration should give a due consideration as well, to be minimizing the number of the traffic accidents. There should be decisive practical measures to stop these accidents.